Sample-by-sample and block-adaptive robust constant modulus-based algorithms - Elnashar, A.; Elnoubi, S.; Elmikati, H. (IET signal processing, 2012)
In this study, a robust sample-by-sample linearly constrained constant modulus algorithm (LCCMA) and a robust adaptive block-Shanno constant modulus algorithm (BSCMA) are developed. The well-established quadratic inequality constraint approach is exploited to add robustness to the developed algorithms. The LCCMA algorithm is implemented, using a fast steepest descent adaptive algorithm, whereas the BSCMA algorithm is realised, using a modified Newton's algorithm without the inverse of Hessian matrix estimation. The developed algorithms are exercised to cancel the multiple access interference in a loaded direct sequence code division multiple access (DS/CDMA) system. Simulations are presented in a rich multipath environment with a severe near-far effect to evaluate the robustness of the proposed DS/CDMA detectors. Finally, a comprehensive comparative analysis between the sample-by-sample and block-adaptive constant modulus-based detectors is presented. It has been demonstrated that, the developed robust BSCMA detector offers rapid convergence speed and very low computational complexity, whereas the developed robust LCCMA detector engenders about 5 dB improvement in the output signal-to-interference-plus-noise ratio over the BSCMA detector.